Competitive advantage of German renewable energy firms in Russsia: An empirical study based on Porter's diamond - Corinna Dögl; Dirk Holtbrügge (Journal for East European Management Studies, 2010)
This article analyzes the competitive advantage of German renewable energy firms in Russia. Based on Porter's diamond model of competitiveness, we examine the demand for renewable energy in Russia and German firms' ability to meet this demand. While the overall demand for renewable energy in Russia is still low, the study reveals formidable opportunities in the fields of biomass, solar and wind energy. Our findings are meant to address managers in the renewable energy industry and to aid policy makers in environmental support and action. – – Dieser Artikel analysiert die Wettbewerbsvorteile deutscher Unternehmen im Bereich erneuerbarer Energien in Russland. Basierend auf Porter's Diamantansatz untersuchen wir die Nachfrage nach erneuerbaren Energien in Russland und die Fähigkeit deutscher Unternehmungen, diese zu bedienen. Während die Nachfrage nach erneuerbaren Energien in Russland insgesamt noch auf einem niedrigen Niveau ist, zeigt die Studie im Bereich Biomasse, Solar- und Windenergie beträchtliche Marktchancen auf. Die Ergebnisse der Studie haben zahlreiche Implikationen für Manager von Unternehmungen im Bereich erneuerbarer Energien und für politische Entscheidungsträger im Energie- und Umweltsektor.
Keywords: 650; Renewable energy; Russia; Porter's diamond